Histories of Sexology
XXX, 298 p. 1 illus.
Keywords: Histories of Sexology: Between Science and Politics takes an interdisciplinary and reflexive approach to the historiography of sexology. Drawing on an intellectual history perspective informed by recent developments in science and technology studies and political history of science, this book examines specific social, cultural, intellectual, scientific and political contexts that have given shape to theories of sexuality, but also to practices in medicine, psychology, education and sexology. Furthermore, it explores various ways that theories of sexuality have both informed and been produced by sexologies—as scientific and clinical discourses about sex—in Western countries since the 19th century. Alain Giami is Emeritus Research Professor at Inserm (National Institute of Health and Medical Research) in Paris, France. Sharman Levinson is Associate Professor at the University of Angers, France, where she specializes in history of French physiology and psychology.